"The home, the bathroom, the taps, and hot water": The contextual characteristics of tap water scalds in Australia and New Zealand. Issue 4 (June 2022) - Singer, Yvonne; Tracy, Lincoln M.; Menezes, Hana; Cleland, Heather; Perrett, Tracey; Wood, Fiona; Harvey, Lara
Highlights: Almost all tap water scalds occurred at home, in the bathroom, while bathing. Over 55% of injuries involved accidental alteration of water temperature. Tap water scalds occur most frequently in young infants and older adults. More older Australians sustained tap water scalds than older New Zealanders. Length of stay is twice as long for tap water scalds compared to other burns. Abstract: Introduction: Scalds from hot tap water can have devastating consequences and lifelong impact on survivors. The aims of this study were to (i) describe the frequency, demographic profile, injury event characteristics, and in-hospital outcomes for people with tap water scalds admitted to Australian and New Zealand burn centres; and (ii) determine whether variation was present in the frequency and epidemiological characteristics of tap water scalds between jurisdictions. Methods: Data were extracted from the Burns Registry of Australia and New Zealand for people with tap water scalds admitted to Australian or New Zealand burn centres between January 1, 2010 and December 31, 2018. Demographic, injury severity and event characteristics, surgical intervention, and in-hospital outcomes were investigated. Results: We included 650 people with tap water scalds admitted to Australian and New Zealand burn centres during the study period. Australians with tap water scalds (median [IQR] 29 [1–69] years) were older than New Zealanders (2 [1–36] years). Most tap water scalds occurred in the home, and 92% of these occurred in the bathroom. More than 55% of injuries occurred due to the accidental alteration of water temperature at the tap fixture. Two thirds of patients underwent a surgical wound procedure. The overall mortality rate was 3.7%, and the median hospital length of stay was 8.8 days. Conclusion: Tap water scalds remain a public health problem in Australia and New Zealand. Our research highlights where gaps in current heated water regulations in residential homes perpetuate risks of tap water scalds, particularly in high-risk groups at the extremes of age. Extending current heated water regulations to include all Australia and New Zealand homes is urgently needed in conjunction with design safety improvements, and ongoing education of key stakeholders.